Short-term preoperative smoking cessation and post-operative pulmonary complications in patients undergoing elective non-cardiac surgery - Balanag, Vincent M.
Study Objective: To determine the effect of short-term smoking cessation on the incidence of postoperative pulmonary complcations (POPC) among patients undergoing elective non-cardiac surgery. Design: Prospective cohort study. Setting: 5 Metro-Manila hospitals (East Avenue Medical Center, Veterans Memorial Medical Center, Lung Center of the Philippines, Capitol Medical Center and Philippine General Hospital). Patients: 237 patients aged 18 years and above who smoked cigarettes within 8 weeks of scheduled elective non-elective surgery; excluded were cigar or pipe smokers, patients for obstetrical procedures or repeat operations, or those with active respiratory problems at the time of evaluation. Measurements and results: Information on demographic and clinical characteristics, smoking history (including presence of nicotine withdrawal symptoms and duration of smoking cessation before surgery) was collected preoperatively. Intraoperative conditions and occurrence of postoperative pulmonary complications (pneumonia, tracheobronchitis, atelectasis, respiratory failure, bronchospasm and postoperative fever) during the first 7 days after surgery were then recorded. Study subjects were classified according to duration of smoking cessation into current smokers, defined as those who smoked within 2 weeks prior to the operation; recent smokers, those who abstained for 2-4 weeks and ex-smokers, those who stopped smoking for 4-8 weeks before surgery. The over-all rate of POPC in the study cohort was 21.1%, with atelectasis and tracheobronchitis as the most frequently recorded respiratory event. The incidence of POPC among current smokers, recent smokers and ex-smokers was 16.6%, 33.3%, and 25%, respectively. After controlling for confounding variables (ASA classification, presence of lung disease, smoking history, and type of surgery) and other independent risk factors (sex, use of general anesthesia and intraoperative blood loss), the odds ratios for POPC for recent smokers and ex-smokers compared to current smokers were 1.45 (95%CI, 0.52 to 4.03) and 1.39 (95%CI, 0.46 to 3.38), respectively. Conclusions: The findings suggest that there are no significant changes in the risk of POPC after smoking cessation of up to 8 weeks in patients undergoing elective non-cardiac surgery. Further studies are needed to confirm these findings.
Thesis (MS Clinical Epidemiology)--University of the Philippines Manila.
Keywords: Cigarette smokers -- Surgery -- Complications